Financial Market Integration Between Stock Market From North American Free Trade Agreement (NAFTA) Member - Yasir Maulana; Wely Hadi Gunawan (Jurnal Akuntansi dan Pajak, 2021)
Economic recession or crisis could show a higher possibility of financial crisis transmission in an integrated stock market. Integration between financial markets is a channel of spreading the devastating effects of the crisis. The objective of this study is to detect significant interactions among the stock markets of countries that are members of the North American Free Trade Agreement (NAFTA). NAFTA is a regional partnership with members from the United States, Canada and Mexico that are committed to reducing trade and investment barriers between member countries. The methodology of this research with VAR VECM model consists of three stages, the first analysis of the presence impact of the stock market index using the Granger Causality Test. Second, analyze the speed of response of an index to a change / shock in another index using the Impulse Response Function (IRF). The third stage analyzes the impact of changes / shocks from one index to other indices by using Variance Decomposition. From the 5 sets of stock market data for NAFTA countries, the results of the study show that there is only one cointegration. When viewed in the cointegration process of each of the two data series, cointegration occurs between the Nasdaq index with TSE and Nasdaq with MSE. Whereas TSE and MSE did not find any cointegration.